Subject attribute in the French Language and its Equivalents in the Macedonian Language - Milena Kasaposka-Chadlovska (University St.Kliment Ohridski-Bitola, 2014)
The function of subject attribute in the French language presents a basic function which is in direct dependence of the verb and the removal of which makes the sentence ungrammatical. In contrast, in the Macedonian language, the attribute is a secondary sentence member, the removal of which does not lead to change in the basic sentence structure. Therefore, our goal in this research paper is to use examples from the French language, in which subject attribute is used, in order to analyse which are its equivalent structures in the Macedonian language, starting from the presumption that the thing defined as subject attribute in the French language, in most of the cases in the Macedonian language would correspond to the nominal part of the verbal-nominal predicate (attribute in English).
Keywords: Subject attribute, French language, Macedonian language, nominal part of the verbal-nominal predicate.